Peningkatan Kompetensi Kader Posyandu Lansia Dalam Merawat Luka - Meiliani Yulis, Dian; Fitriyani, Lia; Purwoto, Ady; Cholifatul Izza, Nurril; Fahri, Ahmad; Suprapto, Suprapto (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Background: Health development is a way to increase awareness, willingness, and ability to live a healthy life for everyone to realize an optimal degree of public health. Attitudes, skills, and knowledge in the implementation of public health activities. Objective: This service improves the competence of elderly posyandu cadres in caring for wounds. Method: Used in this devotion health counseling. As a measuring tool to assess the effectiveness of the counseling, pre-test, and post-test questions is given. Results: Devotion showed an increase in respondents' knowledge before and after the provision of health education. Conclusion: The knowledge of the respondent's diabetes wounds after being given health education has increased. So the existence of health education can affect the knowledge of the elderly. It is hoped that after being given public health counseling, they can apply the education given to minimize the risk of complications of diabetic wounds.